2015
DOI: 10.1111/2041-210x.12422
|View full text |Cite
|
Sign up to set email alerts
|

Faecal cortisol metabolites to assess stress in wildlife: evaluation of a field method in free‐ranging chamois

Abstract: 1. Non-invasive faecal cortisol metabolite (FCM) analysis is a well-established tool to quantify stress in captive and free-ranging species. While the method has great potential, its suitability in field studies might be limited when faecal samples from unknown individuals are used. Possible factors affecting final results and thus jeopardizing correct data interpretation are individual and sex-specific variation, storage conditions and uneven distribution of metabolites in the faeces. 2. We tested these facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 36 publications
0
38
1
Order By: Relevance
“…Previous studies showed that many endogenous and exogenous factors can affect the concentration of faecal corticosteroid metabolites (hereafter referred to as FCM levels) (Hadinger, Haymerle, Knauer, Schwarzenberger, & Walzer, ). In free‐living animals, FCM levels can be affected by food availability (Jenni‐Eiermann, Glaus, Grübler, Schabl, & Jenni, ; Schoech, Bowman, Bridge, & Boughton, ), with increased food availability being associated with lower FCM levels (Jenni‐Eiermann et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that many endogenous and exogenous factors can affect the concentration of faecal corticosteroid metabolites (hereafter referred to as FCM levels) (Hadinger, Haymerle, Knauer, Schwarzenberger, & Walzer, ). In free‐living animals, FCM levels can be affected by food availability (Jenni‐Eiermann, Glaus, Grübler, Schabl, & Jenni, ; Schoech, Bowman, Bridge, & Boughton, ), with increased food availability being associated with lower FCM levels (Jenni‐Eiermann et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this variety of drivers and associated sources of variance, most studies focus only on a small number of factors to assess their hypothesized effect on FCM levels. Inter‐ and intra‐individual differences are often neglected (Goymann, ; Hadinger et al., ; Rehnus & Palme, ). Especially when non‐invasive sampling methods are used, it is often unknown how many individual animals of a population have been sampled and possible pseudo‐replication cannot be excluded (Rehnus & Palme, ).…”
Section: Introductionmentioning
confidence: 99%
“…Other factors such as circadian patterns can also seriously influence plasma GC concentrations (Sheriff et al., ). Noninvasive stress monitoring of wildlife using fecal glucocorticoid metabolites (FGCM) has proved to be a powerful tool and is currently being used increasingly (Hadinger et al., ; Keay et al., ; Millspaugh & Washburn, ; Morrow, Kolver, Verkerk, & Matthews, ; Mostl et al., ). Such measurements preclude some of the above‐mentioned problems as feces can be collected easily without disturbing the animal, allowing repeated sampling for monitoring purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Other factors such as circadian patterns can also seriously influence plasma GC concentrations (Sheriff et al, 2011). Noninvasive stress monitoring of wildlife using fecal glucocorticoid metabolites (FGCM) has proved to be a powerful tool and is currently being used increasingly (Hadinger et al, 2015;Keay et al, 2006;Millspaugh & Washburn, 2004;Morrow, Kolver, Verkerk, & Matthews, 2002;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation